Technical guidelines for enhancing privacy and data protection in modern electronic medical environments. - Gritzalis, S.
Raising awareness and providing guidance to on-line data protection is undoubtedly a crucial issue worldwide. Equally important is the issue of applying privacy-related legislation in a coherent and coordinated way. Both these topics gain extra attention when referring to medical environments and, thus, to the protection of patients' privacy and medical data. Electronic medical transactions require the transmission of personal and medical information over insecure communication channels like the Internet. It is, therefore, a rather straightforward task to capture the electronic medical behavior of a patient, thus constructing "patient profiles," or reveal sensitive information related to a patient's medical history. The consequence is clearly a potential violation of the patient's privacy. We performed a risk analysis study for a Greek shared care environment for the treatment of patients suffering from beta-thalassemia, an empirically embedded scenario that is representative of many other electronic medical environments; we capitalized on its results to provide an assessment of the associated risks, focusing on the description of countermeasures, in the form of technical guidelines that can be employed in such medical environments for protecting the privacy of personal and medical information.
Keywords: EU directives 2002/58.; EU directives 95/46.; EU directives 97/66.; Internet; Beta-thalassemia.; Data security; Electronic medical transaction; Insecure communication channel; Medical information transmission; Modern electronic medical environment; On-line data protection; Patient data privacy enhancement; Patient treatment; Personal information transmission; Privacy-related legislation; Technical guidelines